Haplophyllum sahinii (Rutaceae), a new species from Central Anatolia (Turkey) - Tugay, Osman; Ulukuş, Deni̇z (Phytotaxa, 2017)
Haplophyllum sahinii (Rutaceae) is described and illustrated as a new species, growing in the rocky fields near the village of Apasaraycık-Apa (Konya), in Central Anatolia. It is compared with the similar H. vulcanicum from Karadağ (Karaman) in south-central Turkey, from the point of view of plant, pollen and seed morphology. Some morphological characters of leaves, bracts, petals, ovary and capsule appendage are diagnostic in distinguishing the two species. Distribution map, and description of seed and pollen characters of the new species, are also given.